Continuum Robot Segments With High Output Stiffness via Diagonal Backbones - Eisenhauer, Ethan; Milam, Eli; Gaston, Joshua; Rucker, Caleb (IEEE robotics and automation letters, 2026)
Continuum robots offer unique advantages for applications such as minimally invasive surgery, navigation through confined environments, and safe human-robot interaction. However, while most continuum robot segments are designed to exhibit constant curvature over their length, they passively deform into a non-constant curvature s-shape when holding payloads at the tip, and their dynamic movement is often subject to unwanted vibration of the passive non-constant curvature modes. In this letter, we propose a simple solution to dramatically improve these issues: a continuum robot segment design that utilizes a diagonal backbone and flexible push-pull actuation rods. This simple modification to common continuum-robot construction enables us to eliminate the passive s-shaped mode, creating a bending segment that can handle large loads without significant deformation or vibration while requiring no more actuation force than conventional designs. We show that a modified version of 1-DOF constant-curvature kinematics accurately describes the structure when actuator translations are equal and opposite. We also develop and validate a 2-DOF model that predicts tip position and orientation resulting from more general actuation inputs. The models and increased output stiffness were verified experimentally and the concept was demonstrated on a multi-segment robot following a 3D trajectory with minimal disturbance from added loads.